The Heidenhain variant of Creutzfeldt-Jakob disease and concomitant tau pathology: A case report. - Ehler, Edvard; Pipka, M; Meleková, A; Mandysová, Petra; Johanidesová, S; Matěj, R; Rusina, R (My University, 2017)
Abstract The Heidenhain form of Creutzfeldt-Jakob disease (CJD) is a rare CJD variant with predominantly visual symptoms in the early stages. Clinical manifestations of metamorphopsia, hemianopia and Balint's syndrome correlate with the involvement of the posterior cortical regions. A 71-year old healthy and very active man was admitted because of impaired visual acuity, hemianopia, and gait disturbance progressing over one week. MRI found typical cortical hyperintensities in the occipital regions while rhythm slowing and sharp waves were seen in the occipital regions on EEG. Protein 14-3-3 was detected in the cerebrospinal fluid. Postmortem neuropathology revealed typical histopathological changes consistent with CJD. Moreover, we found deposits of phosphorylated tau protein in the limbic regions that met the criteria for primary age-related tauopathy (PART); representing an additional and interesting finding in our case.
Heidenhainova forma Creutzfeld-Jakobovy nemoci apřídatná tau patologie: kazuistika
Keywords: Creutzfeldt–Jakob disease; Heidenhain variant; Prion; Visuospatial dysfunction; Creutzfeld-Jakobova nemoc, vizuospaciální dysfunkce, Heidenhainova varianta